2016
DOI: 10.1038/srep26072
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27a Induces Mesangial Cell Injury by Targeting of PPARγ and its In Vivo Knockdown Prevents Progression of Diabetic Nephropathy

Abstract: MicroRNAs play important roles in the pathogenesis of diabetic nephropathy (DN). In this study, we found that high glucose upregulated miR-27a expression in cultured glomerular mesangial cells and in the kidney glomeruli of streptozotocin (STZ)-induced diabetic rats. miR-27a knockdown prevented high glucose-induced mesangial cell proliferation and also blocked the upregulation of extracellular matrix (ECM)-associated profibrotic genes. Reduction of cell proliferation and profibrotic gene expression by a miR-27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 40 publications
1
44
0
Order By: Relevance
“…20, 26 In this study, our aim was to explore whether miR-27a promotes podocyte injury through PPAR γ -mediated β -catenin activation in DN.…”
mentioning
confidence: 99%
“…20, 26 In this study, our aim was to explore whether miR-27a promotes podocyte injury through PPAR γ -mediated β -catenin activation in DN.…”
mentioning
confidence: 99%
“…And, micro-RNA23 can be mediated by PPARc in renal calcium oxalate crystal formation. lncRNA TUG1 could modulate ECM accumulation in DN by regulating miR-377 targeting PPARc [48][49][50]. However, the role of the epigenetic modification in PPARc function in kidney diseases still needs further exploration.…”
Section: Pparγ and Kidney Fibrosismentioning
confidence: 99%
“…There is in vivo evidence that microRNA (miR)-29c knockdown or miR-27a knockdown compromises progression of diabetic nephropathy. [8,9] Furthermore, Chien et al [10] have found that miR-21, miR-29a/b/c, and miR-192 are involved in pathogenesis of diabetic neuropathy and might be suggested as biomarkers of progression of diabetic neuropathy. Despite these achievements, the molecular mechanisms behind the diabetic neuropathy have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%